Being a Jew in each Moroccan Protectorate in the 1920’s: The nationalization issue - Touboul, Eva (Hispania Nova, 2021)
In the 1920’s French and Spanish Protectorates in Morocco have to face the same issue: the administrative status of a Jewish population that was much more westernized than the indigenous Muslims. Jewish institutions in France as well as philosephardistic supports in Spain refer to Jewish status in Argelia to call for a massive nationalization. However, for different reasons the decisions made by Paris and Madrid will lead to keeping the Jews from Morocco in an confuse administrative situation.
Keywords: Moroccan Protectorate; France; Spain; jews; sephardism; Alliance Israélite Universelle; nationalization